Navigating the Dual Role of Clinician-Researcher in Qualitative Dental Research. (April 2022) - Geddis-Regan, A.R.; Exley, C.; Taylor, G.D.
In qualitative research, the researcher is the research instrument. Therefore, a qualitative researcher who is also a clinician must consider how their dual position informs participant consent, data collection, and analysis. This reflexivity is essential in research design to effectively respond to ethical questions around role, authenticity, trust, and transparency around disclosing their clinician status to participants.